Metabolic effects of amoebic gill disease (AGD) and chloramines-T exposure in seawater-acclimated Atlantic salmon Salmo salar - Melanie Leef; Harris, JO; Powell, MD (2007)
ABSTRACT: Our aim was to determine possible metabolic effects amoebic gill disease (AGD) on Atlantic salmon Salmo salar. Standard (RS) and routine (RROU) metabolic rates were evaluated by continually measuring oxygen consumption in 2 independent tanks of fish (18.69 ± 1.01 kg m–3, mean ± SE). Active metabolic rate (RACT) and metabolic scope (RACT – RS) were assessed using a chasing protocol and determined at 3 time periods: (1) pre-infection, (2) 3 d post-infection, and (3) 2 d post-treatment. On Day 3 of the study, the fish were infected with amoebae isolated from the gills of AGDaffected salmon (2300 cells l–1). No significant elevations in RACT or metabolic scope were detected 3 d post-infection and 2 d post-treatment; however, significant elevations in RS and RROU were detected 3 d post-infection and 2 d post-treatment. Assessment of RROU data, especially for the light period, also indicated a rise in oxygen consumption rate over the course of the experiment. Treatment of AGD-affected Atlantic salmon with chloramine-T (CL-T) appeared to briefly mitigate the rise in RS, as there was a 30% drop (though non-significant) in RS following treatment. Despite this, RS continued the upward trend 1 d following treatment. These results suggest that over the course of AGD development, RS in Atlantic salmon increases. Therefore, considering the physical conditions which constrain RACT, we expect that metabolic scope would become compromised in fish more heavily affected with AGD. Treatment with CL-T shows promise for mitigating the respiratory effects of AGD and potentially minimising the loss of metabolic scope. KEY WORDS: Amoebic gill disease · AGD · Oxygen uptake · Metabolic scope · Chloramine-T · Atlantic salmon